2017
DOI: 10.3892/ijmm.2017.3329
|View full text |Cite
|
Sign up to set email alerts
|

2,3,5,4'‑Tetrahydroxystilbene‑2‑O‑β‑D‑glucoside inhibits septic serum‑induced inflammatory injury via interfering with the ROS‑MAPK‑NF‑κB signaling pathway in pulmonary aortic endothelial cells

Abstract: Sepsis is characterized by injury to the microvasculature and the microvascular endothelial cells, leading to barrier dysfunction. However, the specific role of injury in septic endothelial barrier dysfunction remains to be elucidated. In the present study, it was hypothesized that endothelial cell inflammatory injury is likely required for barrier dysfunction under septic conditions in vitro. 2,3,5,4'‑Tetrahydroxystilbene‑2‑O‑β‑D‑glucoside (TSG), a compound extracted from Chinese herbs, is able to inhibit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…From this viewpoint, asthma treatment using PM extract has the potential to cause various side effects. Nevertheless, PM has various biological effects [13,14,15,16] and 2,3,5,4′-tetrahydroxystilbene-2-O-β- d -glucoside (TSG) as a main single compound has anti-inflammatory effects [14] and anti-osteoporosis effect [13]. In the present study, we investigated the effects of TSG on asthma as one of the inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this viewpoint, asthma treatment using PM extract has the potential to cause various side effects. Nevertheless, PM has various biological effects [13,14,15,16] and 2,3,5,4′-tetrahydroxystilbene-2-O-β- d -glucoside (TSG) as a main single compound has anti-inflammatory effects [14] and anti-osteoporosis effect [13]. In the present study, we investigated the effects of TSG on asthma as one of the inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies have emphasized the benefits of PM in the treatment of a variety of diseases, such as cancer, diabetes, alopecia, atherosclerosis, and neurodegenerative diseases [11]. 2,3,5,4′-tetrahydroxystilbene-2-O-β- d -glucoside (TSG) is known as a major active single compound of PM [12], and presents a variety of biological effects, such as anti-osteoporosis [13], anti-inflammation [14], kidney protection [15], anti-cancer [16], and liver protection effects [17]. However, Lei et al reported that PM extracts have hepatotoxicity [18], and this is probably due to the cis isomer of TSG [19].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroprotective effects of TSG against glutamate or H 2 O 2 -induced oxidative toxicity were confirmed between cell lines or rodent models [ 7 , 8 ]. Li et al [ 9 ] confirmed that TSG decreased pulmonary aortic endothelial cell inflammatory injury induce by septic-serum via the ROS/MAPK/NF-κB signaling pathway. However, the protective effect of TSG on H 2 O 2 -induced oxidative damage remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%